Análisis estructural horizontal de un bosque secundario. Puerto Almendra, Loreto, Perú – 2014 - Mosquera Fatama, Richardson Steve (2015)
The objective of the study was to know the horizontal structure of a secondary forest of the Forestry Research and Teaching Center (CIEFOR- Puerto Almendra) with the purpose of strengthening the management of forest resources, thus contributing to the conservation, protection, restoration, improvement and proper forest management; Floristic composition, abundance, frequency, dominance and the Importance Value Index (IVI) were recorded. For the evaluation of the floristic structure of forest species, a total of 6 plots, each of approximately 1 hectare (100m x 100m), have been considered as samples. The results indicate that a total of 2838 individuals with DAP greater than 10 cm have been inventoried, grouped into 131 forest species identified by their common names, which are in the following order: Eschweilera albiflora “machimango”, Inga sp. “shimbillo”, Dacryodes peruviana “copal”, Thyrsodium spruceanum “huira caspi”, Hevea brasiliensis “shiringa”, among others.